2020
DOI: 10.1093/ajcn/nqaa259
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge gaps in understanding the metabolic and clinical effects of excess folates/folic acid: a summary, and perspectives, from an NIH workshop

Abstract: Folate, an essential nutrient found naturally in foods in a reduced form, is present in dietary supplements and fortified foods in an oxidized synthetic form (folic acid). There is widespread agreement that maintaining adequate folate status is critical to prevent diseases due to folate inadequacy (e.g., anemia, birth defects, and cancer). However, there are concerns of potential adverse effects of excess folic acid intake and/or elevated folate status, with the original concern focused on exacerbation of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 146 publications
1
116
0
Order By: Relevance
“…Vegans had higher folate intake and concentration than omnivores, and four out of six vegans had levels above the reference range 208–972 nmol/l. Although high folate status is traditionally considered to have positive health effects, recent studies have raised concerns on possible adverse effects of high folate status combined to low vitamin B12 status on neurocognitive health and birth outcomes (Maruvada et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Vegans had higher folate intake and concentration than omnivores, and four out of six vegans had levels above the reference range 208–972 nmol/l. Although high folate status is traditionally considered to have positive health effects, recent studies have raised concerns on possible adverse effects of high folate status combined to low vitamin B12 status on neurocognitive health and birth outcomes (Maruvada et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study, to our knowledge, to report this observation in folic acid-supplemented children with sickle cell disease, which is of note as UMFA has been proposed to be a biomarker of excess folic acid intake (36). A recent National Institutes of Health (NIH) Workshop (2020) on understanding the metabolic and clinical effects of excess folates/folic acid has identified that the evidence on possible adverse effects of excess folate and/or UMFA remains inconclusive, but there is an emerging need to address these gaps in the literature (37). Previous studies have reported an association between excess folic acid intakes and colorectal (38) and prostate (39) cancer in adults, impaired cellular immunity [reduced natural killer cell cytotoxicity in adults, and potential effects on the mucosal immune tissue of the gut in children (40,41)], and adverse effects on metabolic health during development (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Since folate is an important methyldonor for periconceptional epigenetic programming, high doses of folic acid can induce variations in the epigenome of the offspring [ 34 , 118 ]. Until now, there is no conclusive evidence which dose of folic acid supplement use causes adverse effects in either the pregnant woman or the fetus [ 119 ].…”
Section: Considerations For Advising Higher Doses Of Folic Acid Sumentioning
confidence: 99%